Improving inference and forecasting in VAR models using cross-sectional information - Jan Prüser; Boris Blagov (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
We propose a prior for VAR models that exploits the panel structure of macroeconomic time series while also providing shrinkage towards zero to address overfitting concerns. The prior is flexible as it detects shared dynamics of individual variables across endogenously determined groups of countries. We demonstrate the usefulness of our approach via a Monte Carlo study and use our model to capture the hidden homo- and heterogeneities of the euro area member states. Combining pairwise pooling with zero shrinkage delivers sharper parameter inference that improves point and density forecasts over only zero shrinkage or only pooling specifications, and helps with structural analysis by lowering the estimation uncertainty. – – Wir entwickeln einen Prior für VAR-Modelle, der die Panel-Struktur makroökonomischer Zeitreihen berücksichtigt und gleichzeitig eine Schrumpfung gegen Null vorsieht, um Bedenken hinsichtlich eines Overfitting zu begegnen. Der Prior ist flexibel, da er die gemeinsame Dynamik einzelner Variablen in endogen bestimmten Ländergruppen erkennt. Wir demonstrieren die Vorteile unseres Ansatzes anhand einer Monte-Carlo-Studie und verwenden unser Modell, um die verborgenen Homo- und Heterogenitäten der Mitgliedstaaten des Euroraums zu erfassen. Die Kombination von paarweisem Pooling mit Nullschrumpfung liefert eine schärfere Parameterinferenz, die Punkt- und Dichteprognosen im Vergleich zu reinen Nullschrumpfungs- oder reinen Pooling-Spezifikationen verbessert, und hilft bei der Strukturanalyse, indem sie die Schätzunsicherheit verringert.
Keywords: C11; C32; C53; E37; 330; BVAR; shrinkage; forecasting; structural analysis